KEMAMPUAN MEMBACAKAN TEKS BERITA PADA SISWA KELAS VIII 1 SMP NEGERI 3 KOTA BENGKULU TAHUN AJARAN 2016/2017 - Jenny Yandryati; Gumono Gumono; Agus Joko Purwadi (Universitas Bengkulu, 2017)
The purpose of this study to determine the ability to read news texts on students of class VIII 1 SMP Negeri 3 Kota Bengkulu. The method used in this research is descriptive method with quantitative approach. The population in this study were all students of class VIII SMP Negeri 3 Kota Bengkulu which amounted to 140 students from four classes with 75 male students and 76 female students. This research uses simple random sampling technique to take the chosen people correct by the researcher according to the specific characteristics of the sample, the researchers took 14% of the total population of 20 students. Technique of data collecting is done by observation technique and loud reading test. The data analysis used in this study is simple statistic. The results of this study indicate that, the average ability to read the news text of students of grade VIII 1 SMP Negeri 3 Kota Bengkulu is 55.2 (less).